Household Disintegration: Divorce Factors in a Systematic Review of Contemporary Marital Crisis - PRAMBUDI, LUKMAN (Jurnal Marital: Kajian Hukum Keluarga Islam, 2025)
This journal aims to determine the factors that cause divorce. By using the literature review method or literature review, the author writes down several factors that greatly dominate the occurrence of divorce. The data sources used in this writing are from various reputable articles totaling 3029 articles that are relevant to the topic to be discussed. This journal concludes that first; The moral factor is a form of emotion whose embodiment is jealousy, hurt, anger, revenge and hatred towards other people because they think that other people get what they don't get. Second; The factor of the existence of a third person or environment, in which this actor can originate from a lack of attention between husband and wife, can also be from a lack of inner connection between the two such as a lack of feelings of happiness both physically and mentally for both of them. Third; Economic factors, in which the economic balance in the family has a relationship with family happiness as well as success in business and income of the heads of the household. Fourth; Factors of persecution (domestic violence) which is violent behavior or violent procedures that can injure or abuse. Regarding violence, we often hear the language of domestic violence or domestic violence, where husbands abuse their wives. Fifth; Social and cultural factors, which are also social and cultural factors that cause divorce. Because of the different opinions between the husband and the wife that causes disputes and results in divorce.